Teachers' Beliefs About Learning and Teaching Nature of Science: Professional Development Program - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2019)
The Nature of Science (NOS) is an important component of science literacy, which is the main vision of science teaching programs. In contrast, science teachers face significant problems in transferring the nature of science to classroom practices. Science teachers' classroom practices are influenced by their belief in learning and teaching. Therefore, the development of teachers' beliefs in learning and teaching the NOS is important for the development of classroom practices. Thus, in this research, the effect of a continuing professional development (CPD) program aimed at improving science teachers' professional competences related to the NOS on their beliefs about learning and teaching of the NOS was searched. 18 volunteered science teachers participated in the research. A single group pretest-posttest experimental design was used in the study. The data were collected using the Beliefs About Reformed Science Teaching and Learning (BARSTL)'' developed by Sampson and Benton (2006) and the Scale of Self-Efficacy Belief About Teaching the Nature of Science'' developed by researchers. Pre-test and post-test performances of the teachers were compared using the Wilcoxon test. As a result of the research, it has been shown that the CPD program is effective in developing teachers' self-efficacy beliefs about teaching the NOS and teachers' beliefs for reform approaches. Findings show that science teachers' self-efficacy beliefs are quite high, even though their views on the nature of science are inadequate before the professional development program. There is a risk that teachers who have inadequate views and misconceptions about NOS but who are eager to teach and who have high self-efficacy will be an obstacle to the education of science literate individuals. This has further clarified the need for CPD programs that will enable them to face current misconceptions and support their classroom practices, without compromising teachers' enthusiasm and self-efficacy about NOS that is important component of scientific literacy. For this reason, it has been proposed to increase the number of such professional development programs in accordance with the changing professional development paradigms.
Keywords: Beliefs for reform approach; Nature of science; Professional development program; Self-efficacy; Teacher beliefs; Teacher education; SELF-EFFICACY; CONCEPTIONS; VIEWS; STUDENTS